Strategi Kepala Madrasah Dalam Pengembangan Kompetensi Guru Untuk Peningkatan Mutu Pendidikan - Zainuddin; Atim S (FAI- Undar, 2022)
In line with the formulation of the problem above, this study aims as follows: to determine the understanding, efforts and strategies of the head of madrasah in developing teacher competence and improving the quality of education at MAN 4 Jombang. The research approach uses qualitative (qualitative research), field models (field research). In this study, visits to institutions that are examined at least 2-3 times a week will be carried out, the role as an instrument as well as data collectors is realized by visiting MAN 4 Jombang. The time for site visits begins in February 2020 before the occurrence of Covid-19 until August 2020. Interviews were conducted directly and indirectly (phone) due to the Covid-19 pandemic conditions. With purposive sampling, data was collected by means of in-depth interviews, participant observation and documentation. It was found that the principal's understanding of teacher competence in improving the quality of education at MAN 4 Jombang has thoroughly understood and understood the educational competence, personality competence, social competence and professional competence by combining them according to the environmental conditions of the madrasa in the Mambaul Maarif Islamic Boarding School environment. Efforts made by madraash principals, teachers and schools in fulfilling the requirements to improve the quality of learning are meeting content standards, process standards, graduate competency standards, facilities and infrastructure standards, management standards, financing standards, educators and education personnel standards and educational assessment standards. The Head of Madrasah at MAN 4 Jombang in developing teacher competence for improving the quality of education as the implementation of the main tasks and functions in the leadership of the madrasah principal is to carry out the commitment to school quality assurance.